Effects of Trauma-Hemorrhage and IL-6 Deficiency on Splenic Immune Function in a Murine Trauma Model. (9th February 2012) - Mommsen, P.; Barkhausen, T.; Zeckey, C.; Andruszkow, H.; Krettek, C.; Neunaber, C.
Abstract : Splenic immune function is known to be depressed following hemorrhage. The present study investigates the effects of femoral shaft fracture, isolated or in combination with hemorrhage, on early stage cytokine production capacity of splenocytes and observes the role of IL-6 under these conditions. Male IL-6 knockout (IL-6 −/− ) and wild-type mice (WT) were randomly divided into three groups: sham (S), isolated femoral fracture (Fx), and femoral fracture + volume controlled hemorrhage (TH-Fx) (n = 6 per group). Animals were sacrificed four hours after induction of hemorrhage and fracture. Cytokine release (TNF-α, IL-6, and IL-10) of isolated and LPS-stimulated splenocytes was determined by cytometric bead array. Femoral fracture with or without hemorrhage caused a suppression of in vitro cytokine production capacity of splenocytes at an early posttraumatic stage in WT and IL-6 −/− . In the absence of IL-6, the profile of splenic cytokine secretion is significantly altered, identifying this cytokine as a potential therapeutic target to modulate the posttraumatic immune response.